Inequality in Reading and Math Skills Forms Mainly before Kindergarten: A Replication, and Partial Correction, of "Are Schools the Great Equalizer?". Issue 4 (October 2018) - von Hippel, Paul T.; Workman, Joseph; Downey, Douglas B.
When do children become unequal in reading and math skills? Some research claims that inequality grows mainly before school begins. Some research claims that schools cause inequality to grow. And some research—including the 2004 study ''Are Schools the Great Equalizer?''—claims that inequality grows mainly during summer vacations. Unfortunately, the test scores used in the Great Equalizer study suffered from a measurement artifact that exaggerated estimates of inequality growth. In addition, the Great Equalizer study is dated and its participants are no longer school-aged. In this article, we replicate the Great Equalizer study using better test scores in both the original data and a newer cohort of children. When we use the new test scores, we find that variance is substantial at the start of kindergarten and does not grow but actually shrinks over the next two to three years. This finding, which was not evident in the original Great Equalizer study, implicates the years before kindergarten as the primary source of inequality in elementary reading and math. Total score variance grows during most summers and shrinks during most school years, suggesting that schools reduce inequality overall. Changes in inequality are small after kindergarten and do not replicate consistently across grades, subjects, or cohorts. That said, socioeconomic gaps tend to shrink during the school year and grow during the summer, while the black-white gap tends to follow the opposite pattern.